Microstructure-sensitive modeling of competing failure mode between surface and internal nucleation in high cycle fatigue. (March 2020) - Han, Shiwei; Yang, Xiaoguang; Shi, Duoqi; Miao, Guolei; Huang, Jia; Li, Ruizhi
Abstract: Competing fatigue failure between the surface and internal nucleation has been widely observed in metals under the high cycle fatigue regime. To characterize different boundary conditions in surface and internal grain aggregates, a hybrid statistical volume element model was developed by binding two identical periodic stochastic polycrystal microstructure cubes together and superimposing them with a new 2.5 directional periodic boundary condition afterwards. Additional isotropic elastic media was attached on the surface of the hybrid statistical volume element model to represent the oxide layer formed at elevated temperature. Microstructure-sensitive modeling with a crystal plasticity model was implemented by computing multiple hybrid statistical volume elements under two stress levels. The results implied that grains in the surface volume of the hybrid statistical volume element generally tended to deform more easily than their counterparts in the internal one, and the oxide layer had a weak effect in suppressing the surface deformation. It was also demonstrated that the combination of the 2.5 directional periodic boundary condition, additional oxide layer and nonlinear constitutive model jointly brought stochastic effect into the two identical microstructural cubes. Significant competition between the surface and internal nucleation was captured under both stress levels. Since the detrimental influence of oxidation in accelerating crack formation was not considered, the lifetimes from both types of nucleation were overlaid on each other. Given the disruption of the oxide layer under high stress levels, the simulation reproduced the experimental discovery that the probability of surface nucleation increases with the ascending stress level. It is also clarified that the oxide layer cannot prevent surface nucleation under low stress levels, rejecting the hypothesis of the impact of the oxide layer on complete internal nucleation. Highlights: hybrid microstructural statistical volume element is developed to characterize both surface and internal grain aggregates. Microstructure-sensitive modeling of competing failure modes between surface and internal nucleation has been carried out. The influence of thin oxide layer in suppressing surface nucleation is investigated.